Fjenden hedder Medailler - Skjerk, Ole (Forum for Idræt, 2001)
Idrætshistorisk beskrivelse af idrættens udviklingen og sportificering i slutningen af det 19. århundrede med atletikken i København som eksempel. The Enemy’s name is Medals Around 1900 the connection between sport and outdoor life began to loosen in the sports clubs in Copenhagen. Buildings for indoor sporting activities were constructed and ideas of sporting practice changed. In the first major book about sports in Denmark in the 20th century, Idrætsbogen (Book of Sports) from 1909, American ideas of training which included diet and style of life were rejected, but in the next major book “Den danske Idræts Bog” (Book of Danish Sport) from 1935, training was defined as “systematic practice and a carefully measured way of life”. The idea of sport as an activity that affected a whole way of life was connected to the movement towards indoor sporting activities and both were central parts of a sportification process. The movement had a gender dimension as sportsmen in Copenhagen began to evolve team handball as an indoor wintergame, while female sports clubs practised gymnastics in wintertime and outdoor handball in the summer.